EVALUATION OF BOTTLED WATER QUALITY - Φωτίου E.; Κολοβός N. (Bulletin of the Geological Society of Greece, 2004)
The investigation and the evaluation of the bottled water parameters and their relation to the human health is the main target of this paper. Thirty three samples of bottled water were investigated and the quality parameters were compared according to the standards introduced by EC (instruction 80/778 - 15/07/80) of the drinking water. The physicochemical parameters include pH, conductivity, CI, S04, Si02, Ca, Mg, Na, Κ, F, total hardness and alkalinity.